Preventing muscle wasting by osteoporosis drug alendronate in vitro and in myopathy models via sirtuin‐3 down‐regulation. Issue 3 (6th March 2018) - Chiu, Hsien‐Chun; Chiu, Chen‐Yuan; Yang, Rong‐Sen; Chan, Ding‐Cheng; Liu, Shing‐Hwa; Chiang, Chih‐Kang
Abstract: Background: A global consensus on the loss of skeletal muscle mass and function in humans refers as sarcopenia and cachexia including diabetes, obesity, renal failure, and osteoporosis. Despite a current improvement of sarcopenia or cachexia with exercise training and supportive therapies, alternative and specific managements are needed to discover for whom are unable or unwilling to embark on these treatments. Alendronate is a widely used drug for osteoporosis in the elderly and postmenopausal women. Osteopenic menopausal women with 6 months of alendronate therapy have been observed to improve not only lumbar bone mineral density but also handgrip strength. However, the effect and mechanism of alendronate on muscle strength still remain unclear. Here, we investigated the therapeutic potential and the molecular mechanism of alendronate on the loss of muscle mass and strength in vitro and in vivo . Methods: Mouse myoblasts and primary human skeletal muscle‐derived progenitor cells were used to assess the effects of low‐dose alendronate (0.1–1 μM) combined with or without dexamethasone on myotube hypertrophy and myogenic differentiation. Moreover, we also evaluated the effects of low‐dose alendronate (0.5 and 1 mg/kg) by oral administration on the limb muscle function and morphology of mice with denervation‐induced muscle atrophy and glycerol‐induced muscle injury. Results: Alendronate inhibited dexamethasone‐induced myotube atrophy and myogenic differentiation inhibition in mouse myoblasts and primary human skeletal muscle‐derived progenitor cells. Alendronate significantly abrogated dexamethasone‐up‐regulated sirtuin‐3 (SIRT3), but not SIRT1, protein expression in myotubes. Both SIRT3 inhibitor AKG7 and SIRT3‐siRNA transfection could also reverse dexamethasone‐up‐regulated atrogin‐1 and SIRT3 protein expressions. Animal studies showed that low‐dose alendronate by oral administration ameliorated the muscular malfunction in mouse models of denervation‐induced muscle atrophy and glycerol‐induced muscle injury with a negative regulation of SIRT3 expression. Conclusions: The putative mechanism by which muscle atrophy was improved with alendronate might be through the SIRT3 down‐regulation. These findings suggest that alendronate can be a promising therapeutic strategy for management of muscle wasting‐related diseases and sarcopenia.